ANALISIS STRATEGI BERSAING PT. PERTAMINA RETAIL DALAM MENGHADAPI PERSAINGAN BISNIS HILIR SPBU - , Mirza Rhaditya ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The object of this study is PT. Pertamina Retail which is a subsidiary of PT. Pertamina (Persero) engaging in the gas stations business. This study aims to analyze the external and internal environment of the PT. Pertamina Retail, evaluate the competitive strategy of PT. Pertamina Retail, and identify alternative strategy that can be adopted by PT. Pertamina Retail for competing in the gas stations business in Indonesia. In the analysis of the company's external environment, researcher applies Porter's five forces analysis to identify key success factors in the gas station business. Furthermore, researcher adopts value chain analysis to assess company's internal environment that leads to identification of PT. Pertamina Retail's competitive advantage. Based on the analysis of company's external and internal environment, researcher conducts SWOT analysis to identify strengths and weaknesses of PT. Pertamina Retail, as well as threats and opportunities that are potential for the company. Completions of these three stages of analysis allows the researcher to evaluate existing competitive strategies implemented by PT. Pertamina Retail and identify alternative strategy that can be adopted by PT. Pertamina Retail to increase company's competitiveness in the gas stations business today. From the results of this study, it can be concluded that the product differentiation strategy through the development of non-fuel retail business, is an effective competitive strategy that is currently implemented by PT. Pertamina Retail. Moreover, the company may also develop focused differentiation strategy in alternative fuels as an alternative competitive strategy, such as biofuel and fuel gas. This innovation may result in great competitive advantage for PT. Pertamina Retail as a pioneer in the industry for alternative fuels retailer in Indonesia.